Comparative survey study of the use of a low cost exoscope vs. microscope for anterior cervical discectomy and fusion (ACDF) - Encarnacion Ramirez, Manuel; Peralta Baez, Ismael; Nurmukhametov, Renat; Goncharov, Efgeni; Efe, Ibrahim E.; Sufianov, Albert; Ramirez Pena, Issael (Frontiers in Medical Technology, 2023)
Background Anterior cervical discectomy and fusion (ACDF) is an often performed procedure in spine neurosurgery. These are often performed using an operating microscope (OM) for better illumination and visualization. But its use is limited to the surgeon and the assistant. There is difficulty in maneuvering long surgical instruments due to the limited space available. Exoscope (EX) has been used as an alternative to microscopes and endoscopes. We used an EX in patients undergoing ACDF for cervical spondylotic myelopathy. Methods A prospective comparative trial was conducted to test the safety and usability of a low-cost EX compared to a conventional surgical binocular OM in ACDF. Twenty-six patients with degenerative cervical myelopathy symptoms were operated by ACDF assisted by the EX and OM between December 2021 and June 2022. The authors collected and compared data on operative time, intraoperative hemorrhage, hospital admission, and complications in the two groups. Results There were no statistically significant differences between the two groups in mean operative time, hospital stay, or postoperative complications. The average intraoperative blood loss was significantly more in the OM group. There were no surgical complications related to the use of the EX or OM. The comfort level, preoperative setup and intraoperative adjustment of position and angle of the EX were rated higher than the OM group. The image quality, depth perception, and illumination were rated as inferior to that of the OM. The low-cost EX was rated to be superior to that of the OM with regard to education and training purposes. Conclusion Our study showed that the low-cost EX appears to be a safe and effective alternative for OM-assisted ACDF with great comfort and ergonomics and serves as an essential tool for education and training purposes. However, some limitations of our EX included slightly inferior image quality and illumination when compared with the OM.